Mie-Nyam (Tenggiri Fish Noodles) Business Strategy Spinach in Improving the Competitiveness of Healthy Noodles Based on Processed Fish with The Grand Strategy Matrix - Sumartini, Sumartini; Alvina, Zahriani; Defi, An Naim; Armadani, Novi (Politeknik Kelautan dan Perikanan Dumai, 2024)
This study aims to analyze the business strategy of the innovative product